Science and the Idea of Social Engineering (I): Karl Raimund Popper - Gedutis, Aldis (Sociologija. Mintis ir veiksmas, 2003)
The main objective of this article is critical reconsideration of Popper’s ideas, concerning the influence of science on society and the social engineering. Our aim is the reconstruction of Popper’s counter-arguments against utopian social engineering and arguments for rational and scientific control of open society with the help of the piecemeal social engineering. He claims that the open society has many features in common with the science: both are based upon critical thinking, both are ready to admit their mistakes, both progress through critical discussion. If, according to Popper, reason is the only alternative to violence so far discovered, then the politics of the open society is strongly dependent on the science. Science provides methods and ideas for piecemeal social engineering that successfully solves majority of social and political problems. Therefore, without science, a society cannot be open. We seek at the critical evaluation of practical possibilities to exercise piecemeal social engineering and its obstructions.